Jim Dinsmore letter to Thomas Kent regarding Osprey and Snowy Owl sightings, December 2, 1980 - Dinsmore, James J.et al (1980)
Jim Dinsmore note updates his letter from November 19, 1980 with details about Osprey and Snowy Owl sightings. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed